Synthesis of oleanolic acid hydrazide-hydrazone hybrid derivatives and investigation of their cytotoxic effects on A549 human lung cancer cells - Şenol Halil; Mercümek Berre; Şahin Rabia Büşra; Kapucu Halil Burak; Hacıosmanoğlu Ebru (Results in Chemistry, 2022)
In this study, 13 new hybrid compounds were synthesized starting from the natural product oleanolic acid and their in vitro cytotoxic activities were investigated on the BEAS-2B and A549 cell lines. For this purpose, initially, the secondary OH group at the C3 position of oleanolic acid was protected as methoxy and the carboxyl group was converted to a hydrazide. The hybrid compounds 12(a-m) were synthesized starting from the above hydrazide and using 13 different aromatic aldehydes. The biological activity of the resulting compounds was evaluated with doxorubicin as the standard. The IC50 values of the cytotoxic effects of doxorubicin on the BEAS-2B and A549 cells are 0.09 and 0.14 µM, respectively. The hybrid compounds with the lowest cytotoxicity on the BEAS-2B cells were 12b (IC50 = 2.96 µM) and 12f (IC50 = 2.53 µM). The corresponding cytotoxic activity of the same two compounds on A549 cells was 0.08 and 0.22 µM, respectively. Compound 12b was found to have an equivalent cytotoxic activity to doxorubicin on the A549 cells, whereas its activity on the BEAS-2B cells was determined to be approx. 32 times as less potent as doxorubicin. According to the in vitro test results, the hybrid compound 12b may be a promising candidate for further investigation as an anticancer agent.